Analisis Tahap-Tahap Pengembangan Kurikulum dalam Perspektif Manajemen Pendidikan Islam - Remon Saputra; Wilni Oktavia (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the stages of curriculum development from an Islamic Education Management perspective. The study employed a qualitative approach with a literature study method (library research) sourced from books, scientific journals, proceedings, and academic documents relevant to curriculum development and Islamic education management. Data were analyzed using content analysis techniques through the stages of identification, classification, interpretation, synthesis, and conclusion drawing. The results indicate that curriculum development is a systematic and ongoing process that includes needs analysis, goal formulation, material organization, implementation, and curriculum evaluation. From an Islamic Education Management perspective, each stage of curriculum development is oriented not only toward achieving academic competencies but also toward the integration of spiritual, moral, social, and intellectual values. The research findings confirm that the success of curriculum development is greatly influenced by the quality of planning, educator competence, implementation effectiveness, and ongoing evaluation. Furthermore, the integration of Islamic values ​​throughout the curriculum development process is a key characteristic that distinguishes it from the general curriculum approach. Thus, curriculum development based on Islamic Education Management plays a crucial role in producing competent graduates who are adaptive to change, possessing noble character and social responsibility